The Cyclophilin ROC3 Regulates ABA-Induced Stomatal Closure and the Drought Stress Response of Arabidopsis thaliana - Liu, Huiping; Shen, Jianlin; Yuan, Chao; Lu, Dongxue; Acharya, Biswa R.; Wang, Mei; Chen, Donghua; Zhang, Wei (Frontiers in Plant Science, 2021)
Drought causes a major constraint on plant growth, development, and crop productivity. Drought stress enhances the synthesis and mobilization of the phytohormone abscisic acid (ABA). Enhanced cellular levels of ABA promote the production of reactive oxygen species (ROS), which in turn induce anion channel activity in guard cells that consequently leads to stomatal closure. Although Cyclophilins (CYPs) are known to participate in the biotic stress response, their involvement in guard cell ABA signaling and the drought response remains to be established. The Arabidopsis thaliana gene ROC3 encodes a CYP. Arabidopsis roc3 T-DNA mutants showed a reduced level of ABA-activated S-type anion currents, and stomatal closure than wild type (WT). Also, roc3 mutants exhibited rapid loss of water in leaf than wild type. Two complementation lines of roc3 mutants showed similar stomatal response to ABA as observed for WT. Both complementation lines also showed similar water loss as WT by leaf detached assay. Biochemical assay suggested that ROC3 positively regulates ROS accumulation by inhibiting catalase activity. In response to ABA treatment or drought stress, roc3 mutant show down regulation of a number of stress responsive genes. All findings indicate that ROC3 positively regulates ABA-induced stomatal closure and the drought response by regulating ROS homeostasis and the expression of various stress-activated genes.